Pertimbangan Hakim dalam Menjatuhkan Putusan Tindak Pidana Pengeroyokan: Analisis Hukum Positif dan Tujuan Hukum - muhammad irfansyah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes judicial considerations in sentencing mob assault (pengeroyokan) offenses under Indonesian positive law. This study employs a normative legal research method with statutory and conceptual approaches. The results indicate that judicial considerations rely heavily on proving the elements of Article 466 of the Criminal Code (KUHP), valid evidence, and the perpetrator's guilt. However, differing interpretations of the element